Clinical presentation, differential diagnosis and management of bipolar disorder in children and adolescents: a review - Bez, Jeplin (International Journal of Advances in Medicine, 2021)
Bipolar disorder is a mental illness that causes serious disabilities in both social and work function. The occurrence of this disorder in children and adolescent age group has gained the attention of research workers since the 20th century. The varied clinical presentation of this disorder in comparison to the adult population, as well as the management approaches have been a matter of debate for ages. The aim of the study was to put forward the diagnostic and treatment approaches of bipolar disorder in children and adolescent.